Evaluation of angoff and mapmark standard-setting procedures and considerations in setting cut scores of college admission test - Villas, Jonas P.; Pedrajita, Jose Q.; Abaya, Eufracio C; Magadia, Joselito C.; Salubayba, Teodora M.; Javiniar, Joel C. (Quezon City College of Education, University of the Philippines Diliman, 2018)
The elements of evaluation focused on internal, procedural and external validity, and modelled the effects by means of Many-Facet Rasch Model (MFRM) using 3282 students'data. The study also looked into the considerations of the 63 members of the standard-setting panel and the management committee in recommending and finalizing the cut score. The findings of the study shows that the Mapmark methods has better inter-rater reliability than the Angoff method and the cut scores produced by both methods are statistically different with score that is lower than that of the Angoff methods thus, facilitating a higher passing rate.
Dissertation
Includes bibliographical references (pages 187-197).
Keywords: Universities and colleges -- Entrance examinations. -- Philippines; Rasch model; Many-Facet Rasch Model; Mapmark methods; Angoff methods